2013
DOI: 10.1200/jco.2011.39.9881
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of FOXP3, CD68, and CD20 at Diagnosis in the Microenvironment of Classical Hodgkin Lymphoma Is Predictive of Outcome

Abstract: A B S T R A C T PurposeThe immune microenvironment is key to the pathophysiology of classical Hodgkin lymphoma (CHL). Twenty percent of patients experience failure of their initial treatment, and others receive excessively toxic treatment. Prognostic scores and biomarkers have yet to influence outcomes significantly. Previous biomarker studies have been limited by the extent of tissue analyzed, statistical inconsistencies, and failure to validate findings. We aimed to overcome these limitations by validating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 32 publications
8
122
2
6
Order By: Relevance
“…[35,37,41] In our study, there was association between high CD68+ TAM infiltration and higher disease stage similar to previous reports. [19,35,42,44] In the present study, we demonstrated a positive correlation between high CD68+ TAM infiltration and shortened DFS but not DSS. Several studies (see Table 3) reported association of high CD68+ TAM infiltration with poor survival outcome using DFS, DSS, or overall survival (OS).…”
Section: Discussionsupporting
confidence: 64%
“…[35,37,41] In our study, there was association between high CD68+ TAM infiltration and higher disease stage similar to previous reports. [19,35,42,44] In the present study, we demonstrated a positive correlation between high CD68+ TAM infiltration and shortened DFS but not DSS. Several studies (see Table 3) reported association of high CD68+ TAM infiltration with poor survival outcome using DFS, DSS, or overall survival (OS).…”
Section: Discussionsupporting
confidence: 64%
“…Using 1,700 cells/mm 3 as a cut-off point, patients with high nonfollicular CD20 expression had overall survival improved (p=0.003) at 5 years (87% versus 70%), at 10 years (84% versus 52%) and at 20 years (76% versus 43%). 2 Tzankov et al, in a study with 119 patients with classical HL followed for 12 years demonstrated that immunopheno- type CD30+/CD15±/CD20+ is associated with a favorable clinical outcome and CD20 was an independent positive prognostic factor (p=0.035). Failure-free survival was higher in CD20+ patients (286 months versus 202 months; p=0.022).…”
Section: Anti-cd20 Therapymentioning
confidence: 99%
“…In addition to these malignant cells, HL infiltrates comprise T cells, neutrophils, eosinophils, macrophages, fibroblast, plasma cells and mast cells. 1,2 The malignant cells are referred to as giant cells, also denominated Hodgkin Reed-Sternberg (HRS) cells, and their origin remains controversial. 1 Some theories point to either a fusion of B and non-B cells or mutation in germinal-center cells and loss of B cell receptor expression.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations